Retrospective Analysis of Hashimoto's Thyroiditis in Children and Adolescents: A Single Center Experience - Selma Tunç; Behzat Özkan (Galenos Publishing House, 2021)
Objective: Hashimoto's thyroiditis is an organ-specific autoimmune disease and the most common cause of goiter and acquired hypothyroidism in children and adolescents in regions devoid of endemic iodine deficiency. In this study, it was aimed to examine the epidemiological, clinical and laboratory features of Hashimoto's thyroiditis and autoimmune diseases accompanying Hashimoto's thyroiditis in children and adolescents. Methods: We retrospectively examined thyrotropin, free thyroxin, thyroid autoantibodies (thyroid peroxidase and thyroglobulin antibodies), immunoglobulin A (IgA), anti-tissue transglutaminase antibodies (IgA-tTG), and thyroid ultrasonography findings of 108 cases aged 5-18 years with positive anti-thyroid antibodies. Results: The female/male ratio was 80/28 and 68% of the patients were adolescents. The most common admission complaint was goiter. At the time of diagnosis, the cases had euthyroidism (44.4%), subclinical hypothyroidism (35%), overt hypothyroidism (16.6%), and hyperthyroidism (3.7%). Goiter was detected in 58 (53.7%) cases by thyroid ultrasonography. During the follow-up, overt hypothyroidism developed in 6 patients who had subclinical hypothyroidism and subclinical hypothyroidism developed in 8 patients who had euthyroidism. All patients with hyperthyroidism became euthyroid. Levothyroxine treatment was administered to 47 (43.5%) patients. Celiac disease was detected in 2 and type 1 diabetes mellitus in 1 patient. Conclusions: The prevalence of Hashimoto's thyroiditis increases with age both in childhood and adolescence, and thyroid functions tend to deteriorate over time. Therefore, close follow-up and appropriate treatment are important. Although the prevalence of celiac disease is higher in children and adolescents with Hashimoto's thyroiditis compared to healthy children, the true prevalence of autoimmune diseases accompanying Hashimoto's thyroiditis will be revealed in studies to be conducted in larger patient populations.